2014
DOI: 10.1063/1.4882855
|View full text |Cite
|
Sign up to set email alerts
|

Tailoring structure of inclusion with strain-induced closure to reduce Poisson's ratio of composite materials

Abstract: Tailoring structure of inclusion with strain-induced closure to reduce Poisson's ratio of composite materials A novel 3D continuum shell structure is introduced as inclusion for composite materials with special mechanical properties in this paper. Its geometry is based on a hollow re-entrant tetrahedron. In a composite, such an inclusion can demonstrate a closure effect induced by external compression. Its specific deformation mechanism results in a special character of deformation and affects effective (globa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…In Krödel et al's work, a new design concept for small‐scale lattice materials was proposed, whose effective static and dynamic elastic properties can be controlled relatively independently through careful unit‐cell architecture . In addition, a novel 3D continuum shell structure was introduced as inclusion for composite materials with special mechanical properties by Hou et al . Ge et al reported a new NPR 3D fabric structure for composite reinforcement .…”
Section: Introductionmentioning
confidence: 99%
“…In Krödel et al's work, a new design concept for small‐scale lattice materials was proposed, whose effective static and dynamic elastic properties can be controlled relatively independently through careful unit‐cell architecture . In addition, a novel 3D continuum shell structure was introduced as inclusion for composite materials with special mechanical properties by Hou et al . Ge et al reported a new NPR 3D fabric structure for composite reinforcement .…”
Section: Introductionmentioning
confidence: 99%
“…This study introduces a novel composite structure, which is developed on the basis of a stack of 3D hollow shell inclusions. The concept of the inclusion was introduced in our previous work . However, only a single inclusion was analysed in that study regarding its effects on a composite structure under compressive loading.…”
Section: Discussionmentioning
confidence: 99%
“…The geometry features of the re‐entrant hollow shell inclusions used in the developed composite structure were introduced in our previous work (Fig. ) . To analyse the effects of geometry features of this sort of inclusion, the re‐entrant degree, which is controlled by H , is used as an effective parameter (Fig.…”
Section: Composite Structure and Fe Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…Yet, plenty of reinforcements have been proposed or developed to fabricate auxetic composites, such as specific two-dimensional (2D) triangle inclusions [13,14,15], three-dimensional (3D) tetrahedron hollow shell [16,17], cellular honeycomb structure [18,19], double arrowhead [20,21], and chiral network [22]. Hou et al [14,15,16,17] found that the mechanical properties and deformation behavior of auxetic composites can be tailored by controlling the geometry features and the density of inclusions, and these findings were confirmed by Wang et al [6], Hu [13], and Li et al [18]. Recently, Bruggi et al theoretically investigated the synthesis of auxetic structures by a topology optimization approach for micropolar materials.…”
Section: Introductionmentioning
confidence: 99%